2014
DOI: 10.1039/c4sc01162g
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoromethylated nucleic acid analogues capable of self-assembly through hydrophobic interactions

Abstract: An artificial nucleic acid analogue capable of self-assembly into duplex merely through hydrophobic interactions is presented. The replacement of Watson-Crick hydrogen bonding with strictly hydrophobic interactions has the potential to confer new properties and facilitate the construction of complex DNA nanodevices. To study how the hydrophobic effect works during the self-assembly of nucleic acid bases, we have designed and synthesized a series of fluorinated nucleic acids (FNA) containing 3,5-bis(trifluorome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…The up-field shift of 19 F NMR signals can be explained by the fact that fluorine-rich individual peptide fibers aggregated to form thicker fibrils by a fluorine-fluorine interaction (fluorous effect) during the sonication-induced gelation process. Similar types of fluorine-fluorine hydrophobic interactions were reported by Tan et al 48 . The inter-fibril interaction to form thicker fibrils was also supported by HR-SEM ( Fig.…”
Section: Resultssupporting
confidence: 85%
“…The up-field shift of 19 F NMR signals can be explained by the fact that fluorine-rich individual peptide fibers aggregated to form thicker fibrils by a fluorine-fluorine interaction (fluorous effect) during the sonication-induced gelation process. Similar types of fluorine-fluorine hydrophobic interactions were reported by Tan et al 48 . The inter-fibril interaction to form thicker fibrils was also supported by HR-SEM ( Fig.…”
Section: Resultssupporting
confidence: 85%
“…This phenomenon is explained by the following points. First, F–F base pairs display stronger binding free energies than natural base pairs, 33 providing tighter interaction in the stem region. Second, hydrophobic interactions between fluorinated base pairs show stronger resistance against temperature change compared to hydrogen bonding between natural base pairs.…”
Section: Results and Dissusionmentioning
confidence: 99%
“…33 Based on this observation, we hypothesized that an MB constructed through hydrophobic F–F base pairing would present the following advantages over conventional MBs: (1) enhanced stability against enzymatic degradation by the introduction of artificial base F; (2) resistance to interference with other biomolecules by self-assembly of the stem through hydrophobic interactions instead of hydrogen bonding (Scheme 1). Artificial DNAs may provide promising solutions for challenges strangling wide applications of DNA nanoprobes and nanodevices, and thus we illustrate here the construction of molecular beacons with hydrophobic bases for intracellular imaging.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to conjugation with hydrophobic tails, hydrophobic nucleotide analogues offered an alternative strategy for precise control over the site and the number of hydrophobic tags in the DNA sequence. For example, Wang et al synthesized an artificial nucleotide analogue containing 3,5-bis(trifluoromethyl)benzene (F) that could be accurately incorporated into oligonucleotides through automatic solid-phase DNA synthesis [39,40]. Meanwhile, Abdullah et al synthesized a hydrophobic nucleotide analogue with a ferrocene base (Fc-base) and demonstrated that DNA strands extended with an Fc-base could self-assemble into micelle structures, revealing great potential for cell-surface engineering [41,42].…”
Section: Membrane Functionalization Strategiesmentioning
confidence: 99%